Time series forecasting for tourism industry in Malaysia - Noratikah, Abu; Siti Aishah @Tsamienah, Taib; Nurul Amira, Zainal; Nor Azuana, Ramli; Go, Clark Kendrick (Pushpa Publishing House, 2024)
This study is conducted to forecast the future tourism demand in Malaysia by applying Box-Jenkins modelling. The time series data of tourist arrivals volume in Malaysia before MCO retrieved from MOTAC Malaysia database is implemented in this study. The forecast evaluation methods used to validate the best Box-Jenkins model before proceeding to forecasting stage are MAPE and RMSE, and the analysis was performed by using Python. The findings show that SARIMA (2,1,1)(0,1,1)12 was considered as highly accurate forecasting model based on its least error produced.